The ethical, legal and Islamic perspectives on advance medical directives - Jahn Kassim, Puteri Nemie; Alias, Fadhlina (Jordan Society for Islamic Medical Sciences, Amman-Jordan & Federation of Islamic Medical Associations (FIMA), 2017)
Advance medical directives emerged due to increased focus on greater patient autonomy which has now taken the forefront in medical decision making. An advance medical directive seeks to preserve a patient’s right of self-determination and acts as a guide for doctors to determine medical treatment that represents the patient’s values and wishes when he/she is unable to partake in the decision-making process. It not only fulfils the ethical obligation of doctors in respecting patient's autonomy, but also facilitates the application of the principle of justice in terms of managing health care resources, and helps to alleviate the psychological burden experienced by family members and health care providers. The position of advance medical directives in furtherance of these aims must thus be examined from the ethical, legal and religious perspectives, in order to properly comprehend the nature of such an instrument,and ensure its legitimacy and effective implementation in medico-legal practice.